THE EVIDENCE OF THE MAIN CHARACTERISTICS OF COW MILK IN FUNCTION OF QUALITY CLASS - VIOARA MIREŞAN; CAMELIA RĂDUCU; S. DĂRĂBAN; AURELIA PECE; C. COROIAN (Scientific Papers Animal Science and Biotechnologies, 2023)
The main objective of the researchers was the evidence of phisico-chemical parameters of milk and the classification of it in classes. The quality parameters are given by the number of total germs count (TGC) and number of somatic cells (NSC). These conditions of milk quality should be a guide for every farmer in order to assess the exploitation economicity.